PEMILAHAN JENIS KAYU KAPUR SINTOK (DRYOBALANOPS OOCARPA V. SI.) DARI JENIS-JENIS KAYU KAPUR LAINNYA - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1987)
Kapur sintok  (Dryobalanops oocarpa  V. SI.) is the lightest and also the lowest in durability  among  the nine wood species of kapur.  It is there fore  necessary to separate  this wood species from   the other members,  but  it is difficult   to separate  based  on anatomical  characters.   A chemical spot  test proved  to be simple  and applicable. Kapur  sintok  responded  negatively  to the aplication  of 5 percent of ferric ammonium sulphate  while the other eight species responded positively.